Analisis Perbandingan PSAK No. 18 Tahun 1994 dan Revisi 2010 Serta pengaruhnya Terhadap Laporan Keuangan - Sari, Ervina Indri; Efrianti, Desi (Institut Bisnis dan Informatika Kesatuan, 2014)
The purpose of the study was to determine the comparison between PSAK No. 18 (1994) and PSAK No. 18 (revised 2010), and the effect of PSAK No. 18 changes to the financial statements on PT. TASPEN. Changes in PSAK No. 18 Among other things, the scope of which is wider than the pension fund entities that are analogous to finish work because entering retirement age but completed work in accordance with the plan or contract work. Actuarial present value, is now calculated and reported using current salary levels or projected salary levels up to the time of Retirement attendees. Financial statements, for defined contribution plans and defined benefit plan is split into the separate financial statements. And the presentation of the fair value of investments at fair value. The authors conclude that, given that PSAK No. 18 (revised 2010) came into effect on January 1, 2012, the readiness PT. TASPEN (Persero) in applying PSAK No. 18 (revised 2010) should be considered to receive this new standard.